A rare case of retroperitoneal leiomyosarcoma - Nishal, Arpita J.; Modi, Jigna P.; Shah, Hiral D.; Modi, Rahul A. (International Journal of Research in Medical Sciences, 2017)
Leiomyosarcoma, a rare malignancy of smooth muscle may arise from the retroperitoneum. They often reach a large size before diagnosis is made. Patient presents with vague symptoms, as such retroperitoneal malignancies are related to displacement of organs and obstructive phenomenon. The present paper is one of the very few case reports of retroperitoneal leiomyosarcoma which illustrates the presenting symptoms, gross and microscopic findings, treatment modalities and prognostic indicators of a 70 years old male seen at Government medical college, New Civil Hospital, Surat.